The effect of using STEM PjBL-based science learning modules on students’ participation in the materials of work, energy, and simple machines - Siti Normalisa; Yasmine Khairunnisa; Rizky Febriyani Putri (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
Science learning approaches that are less interactive cause low student participation in education. Therefore, this study investigates an interactive approach, namely the STEM PjBL based science learning module. This study aims to determine the effect of STEM Project-Based Learning (PjBL)-based science learning modules on learner participation in the material of effort, energy, and simple machines. A quasi-experimental quantitative research design was conducted with 61 students divided into experimental groups and control groups, selected through a purposive sampling technique. Data were collected using questionnaires and participant observation sheets that had been tested for validity. Findings showed a significant increase in student participation in the experimental group (80%) compared to the control group (60%). Statistical analysis, including t-test with sig. 0.000 and Pearson’s value correlation test of 0.539 with sig. 0.002, showed a significant difference between the two groups, supporting the effectiveness of the STEM PjBL module. However, this study highlights the limited role of the teacher as a facilitator and the project guidelines in the module are less specific so there are groups that make projects outside the topic. Overall, this study concluded that the use of STEM PjBL-based modules positively influenced students’ participation in science learning.